Relıabılıty of complex ındexes for fluorescent-hyperspectral method for assessıng chlorophyll content ın plant leaves - Касумов, В. А.; Алиева, К. Дж. (Problems of Informatization and Management, 2021)
Analysis of chlorophyll fluorescence parameters is a powerful tool for studying the effects of a wide variety of environmental factors on plant organisms. Chemical factors and climatic conditions, often being inhibitors and activators of bioenergetic processes occurring in the thylakoids of plant cells, are capable of exerting a pronounced effect on the kinetic parameters and spectral features of fluorescence, as well as on its stationary level. Studies of the kinetics of fluorescence can provide important information regarding the nature of the activity of the environmental factor to influence the parameters of photosynthesis – applicable for the purposes of environmental monitoring, as well as for assessing plant resistance. Differential measurements of chlorophyll fluorescence parameters are much less dependent on red light readsorption if the fluorescence kinetics is taken into account. The calculation of most of the vegetation indices is based on the two most stable (independent of other factors) sections of the spectral reflectance curve of plants. The red zone of the spectrum has the maximum absorption of solar radiation by chlorophyll, and the near infrared zone has the maximum reflection of energy by the cellular structure of the leaf. The indices of this group reflect the total amount of vegetation and are used to assess its condition in solving a wide range of problems. They summarize and reflect the influence of factors such as chlorophyll content, leaf surface area, density and structure of vegetation. The main purpose of these indicators is to map the vegetation cover, identify areas covered and not covered with vegetation, assess and monitor the state of the vegetation cover. The use of reflectance values in narrow spectral zones allows the use of indices to register even small changes in the state of vegetation.